Adsorptive removal of Bisphenol a from aqueous solution using activated carbon from coffee residue - Naganathan, Krishanth Kumar (2021)
The present work was aimed to evaluate the performance of low-cost activated carbon from coffee residue for Bisphenol A removal. Coffee residue was activated using phosphoric acid and iron (III) chloride. The resultant activated carbons were characterized for textural properties, surface chemistry and surface morphology. The results show that AC-CoR I (H3PO4-activated coffee residue carbon) exhibits high surface area of 1030 m2/g and mesopore size of 2.13 nm, favourable for Bisphenol A removal at 105 mg/g. The adsorption data fitted well with the pseudo-second-order and Langmuir models. In conclusion, coffee residue is a promising precursor of activated carbon for wastewater treatment.